Synthesis and properties of functional twisted tolanes - Kozhemyakin, Yury; Kretzschmar, Andreas; Krämer, Maximilian; Rominger, Frank; Dreuw, Andreas; Bunz, Uwe H. F. (Chemistry - a European journal, 2017)
The synthesis and optical properties of several novel fluorescent and/or phosphorescent bridged tolanes (tolanophanes) are reported and their optical and structural properties are investigated. Specifically, diiodinated and bisalkynylated tolanophanes were obtained, and characterized by spectroscopy and computational methods. They represent attractive building blocks for novel polymers and emissive solid-state materials.